Development and evaluation of the Coronary Artery Disease Empowerment Scale (CADES) in Korea. (November 2021) - Kim, Jiyoung; Shin, Nayeon; Lee, Kyungmi
The study aimed to develop and test the Coronary Artery Disease Empowerment Scale in Korea and assess its initial aspects of validity and reliability. The participants included 301 patients diagnosed with coronary artery disease, receiving regular outpatient and inpatient care. Data were collected from August to December 2019. The exploratory factor analysis resulted in extracting 25 items and three factors—self-determination, emotional self-regulation, and personal competence of disease management perception—with a cumulative explanatory power of 55.40%. A significant correlation was found between the Korean versions of the Cardiac Self-efficacy Scale ( r  = .31, p  < .001) and the Health Empowerment Scale ( r  = .45, p  < .001). The internal consistency reliability of all items was .93. The developed instrument can be used to evaluate empowerment in patients with coronary artery disease and identify an improved instrument to measure empowerment. However, further testing of the newly developed Coronary Artery Disease Empowerment Scale is required.